(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article explores the fascinating interplay between the English language and the field of fruit and viticulture. From the cultivation of grapes to the description of flavors and aromas, English words have played a significant role in shaping the discourse surrounding fruits and wine. Through an examination of literature and terminology, this article delves into the origins, development, and impact of English words in viticulture, shedding light on their rich history and enduring influence.